FORMULASI FRASA PENCEMARAN NAMA BAIK PADA PASAL 27 AYAT (3) UNDANG-UNDANG NOMOR 11 TAHUN 2008 BESERTA PERUBAHAN PERSPEKTIF FIQH SIYASAH DUSTURIYAH - Artha Prima Putra; Sudi Prayitno (Jurnal Integrasi Ilmu Syariah (Jisrah), 2022)
This article discusses how the formulation of the phrase defamation in Article 27 Paragraph (3) which does not explain what kind of act that leads to defamation is so that this phrase has a very broad meaning and is considered by the community and various circles as a rubber article with multiple interpretations. Several cases that occurred in Indonesia in Article 27 Paragraph (3) gave rise to the diversity of judges in making decisions. This article is a library research using a normative legal approach. This study finds that when viewed in Islamic law the main goal is to form laws to enforce justice and order in society. This justice has also been explained in Law Number 15 of 2019 concerning Amendments to Law Number 12 of 2011 concerning the Establishment of Legislation in Article 6 letter g. Defamation in Islamic law is termed tajassus (finding other people's faults), tahassus (eavesdropping on people's conversations), ghibah (gossip), fitnah (fake news) because of the similarity of illat.